Biophysical Characteristics of Nesting Site of Leatherback Turtles (Dermochelys coriacea) and Olive Ridley Turtles (Lepidochelys olivacea) on Lhoknga Beach of Aceh Besar - Syafrizal Syafrizal; Zuriana Siregar; Aida Fithri; Widya Sari (Elkawnie, 2022)
Abstract: Leatherback turtle (Dermochelys coriaceae) and olive ridley turtle (Lepidochelys olivaceae) are endangered turtle species that continue to experience population decline due to various factors, one of which is the degradation of nesting habitats. A coastal area is commonly used by turtles as a nesting ground as it is associated with the characteristics of the bio-physical environment required for the successful hatching of their eggs. The present study aims to explore turtle nesting habitats related to the bio-physical features of Lhoknga Beach in Aceh Besar. An exploratory survey method was employed. A descriptive data analysis was conducted on the number of eggs and environmental parameters. Around the coastal area, the sand temperature ranges from 28.25 to 28.76oC, the sand humidity ranges from 44% to 52%, the beach width is 15.35 to 27.49 m, the beach slope is 1.68o–4.41o (categorized as gently sloping), and medium-sized sand sediments dominate the beach. Based on the number of turtle nests and eggs, the findings reveal 14 nests and 878 eggs of the leatherback and 5 nests and 533 eggs of the olive ridley turtle. The whole turtles’ nesting habitats and activities discovered on Lhoknga Beach are supported by the favourable biophysical conditions of the coast. A total of 8 species of coastal vegetation and 4 predators are located in the area. Based on the characteristics of the coast, it can be concluded that Lhoknga Beach has suitable coastal features for turtle habitats and can potentially be utilized as a conservation area in Aceh Besar Regency.Abstrak: Penyu belimbing (Dermochelys coriaceae) dan penyu lekang (Lepidochelys olivaceae) merupakan jenis penyu yang terancam punah terus mengalami penurunan populasi yang disebabkan oleh berbagai faktor diantaranya yaitu degradasi habitat peneluran. Kawasan pesisir pantai dimanfaatkan penyu sebagai tempat peneluran (nesting ground) yang berkaitan dengan karakteristik lingkungan bio-fisik pantai berperan penting dalam keberhasilan penetasan telur penyu. Tujuan dari penelitian ini adalah untuk mengetahui kajian habitat peneluran penyu terkait dengan karakteristik bio-fisik pantai di kawasan Pantai Lhoknga Kabupaten Aceh Besar. Penelitian ini dilakukan dengan metode survey exploratif dan analisis data dilakukan secara deskriptif terhadap jumlah telur dan parameter lingkungan. Kondisi suhu pasir pantai berkisar antara 28,25–28,76oC, kelembapan pasir 44%–52%, lebar pantai 15,35 m–27,49 m, kemiringan pantai 1,68o–4,41o (berkategori landai) dan didominasi sedimen pasir dengan ukuran sedang. Berdasarkan jumlah sarang dan telur penyu, ditemukan sebanyak 14 sarang dengan 878 telur pada penyu belimbing dan 5 sarang dengan 533 telur pada penyu lekang. Aktivitas peneluran tersebut didukung dengan kondisi karakteristik biofisik pantai yang dimiliki Pantai Loknga mendukung sebagai habitat peneluran penyu. Vegetasi pantai yang ditemukan terdapat 8 spesies dan predator rantai makanan 4 spesies. Berdasarkan karakteristik pantai yang ditemukan dapat disimpulkan bahwa kawasan Pantai Lhoknga memiliki karakteristik pantai yang sesuai sebagai habitat peneluran penyu dan berpotensi untuk dijadikan sebagai kawasan konservasi penyu di Kabupaten Aceh Besar.